Pengaruh Variabel Makro Suku Bunga, Inflasi, dan Kurs terhadap Indeks Harga Saham Gabungan - RD. Chandra Gunawindharto (Jurnal Pustaka Cendekia Hukum dan Ilmu Sosial, 2024)
The stock exchange becomes one of indicator shown the modernity of one country and investment alternative as well. Stock Exchange activity reflected by an Indonesia Composite Index fluctuation which are influenced by macroeconomics variables such as interest rate, exchange value, and inflation. This study aims to determine the effect of, interest rates, exchange rate of rupiah and inflation against the Indonesia Composite Index(ICI. The type of research used explanatory research, with quantitative approach and took all time series data covering Interest Rates, Rupiah Exchange Rate, Inflation and Indonesia Composite Index(ICI) for the period of 1999 until 2023. The data analysis used multiple linear regression analysis using SPSS 23. The results of this study indicate that the value of coefficient of determination(R2) 86,5% which means independent variables affect the dependent variable 86,5% and the rest is 14,5% influenced by other variables outside this study. F test results indicate that the independent variables of interest rate, exchange rate of rupiah, and inlation rate simultaneously have significant effect on the Indonesia Composite Index(ICI). The result of t test shows that the, interest rate variable partially have significant negative effect on Indonesia Composite Index(ICI), inflation variable partially positively influenced the Indonesia Composite Index(ICI), while exchange rate variable partially have significant positive effeft on Indonesia Composite Index (ICI).